Advances on layered transition-metal oxides for sodium-ion batteries: a mini review - Lu, Jinlin; Zhang, Jinwen; Huang, Yingying; Zhang, Yi; Yin, Yansheng; Bao, Shuo (Frontiers in Energy Research, 2023)
The energy storage mechanism and manufacturing equipment of sodium-ion batteries (SIBs) and lithium-ion batteries (LIBs) are similar. However, SIBs offer several advantages, such as low cost, abundant resources, environmental friendliness, and high safety. Consequently, they have garnered significant attention. SIBs are poised to be potential replacements for LIBs and represent ideal candidates in the field of large-scale energy storage. Layered transition-metal oxides (TMOs) are considered highly promising cathode materials due to their high average voltage, high specific capacity, and ease of synthesis. This paper provides a review of recent advances in layered TMOs for SIBs, including NaxCoO2, NaxMnO2, NaxFeO2, and their derivatives. Furthermore, the challenges and prospects in the development of layered TMOs are also discussed. It is hoped that this review will assist in the design and preparation of SIBs with superior electrochemical performance and further facilitate their practical application.